A High-Precision US-Guided Robot-Assisted HIFU Treatment System for Breast Cancer. (October 2018) - Tang, Tianhan; Azuma, Takashi; Iwahashi, Toshihide; Takeuchi, Hideki; Kobayashi, Etsuko; Sakuma, Ichiro
Abstract: Breast cancer is the most commonly diagnosed cancer in women. A strong treatment candidate is high-intensity focused ultrasound (HIFU), a non-invasive therapeutic method that has already demonstrated its promise. To improve the precision and lower the cost of HIFU treatment, our group has developed an ultrasound (US)-guided, five-degree-of-freedom (DOF), robot-assisted HIFU system. We constructed a fully functional prototype enabling easy three-dimensional (3D) US image reconstruction, target segmentation, treatment path generation, and automatic HIFU irradiation. The position was calibrated using a wire phantom and the coagulated area was assessed on heterogeneous tissue phantoms. Under the US guidance, the centroids of the HIFU-ablated area deviated by less than 2 mm from the planned treatment region. The overshoot around the planned region was well below the tolerance of clinical usage. Our system is considered to be sufficiently accurate for breast cancer treatment.